2018
DOI: 10.1093/abbs/gmy006
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-133a is involved in the regulation of postmenopausal osteoporosis through promoting osteoclast differentiation

Abstract: The important role of miR-133a in the progress and development of postmenopausal osteoporosis has been reported, however, the underlying mechanism is not clear yet. In this study, qRT-PCR analysis was performed to assess miR-133 expression in serum isolated from postmenopausal osteoporosis patients (PMOP) and healthy controls. Bone mineral density (BMD) was measured at the lumbar spine by dual-energy X-ray absorptiometry (DXA). The results showed that miR-133a was significantly upregulated and negatively corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 31 publications
1
71
0
1
Order By: Relevance
“…In the TPTD treatment group, miR‐133a and miR‐33 levels were significantly decreased after 3 to 12 months of treatment. As shown in other human studies, miR‐133a could promote osteoclast differentiation, and its level was correlated with low BMD in postmenopausal women . It was also shown that miR‐133a could hamper bone formation by targeting RUNX2 .…”
Section: Mirnas In Antiosteoporosis Treatmentsupporting
confidence: 56%
See 2 more Smart Citations
“…In the TPTD treatment group, miR‐133a and miR‐33 levels were significantly decreased after 3 to 12 months of treatment. As shown in other human studies, miR‐133a could promote osteoclast differentiation, and its level was correlated with low BMD in postmenopausal women . It was also shown that miR‐133a could hamper bone formation by targeting RUNX2 .…”
Section: Mirnas In Antiosteoporosis Treatmentsupporting
confidence: 56%
“…Using bioinformatics analysis, osteoblast‐related genes, such as CXCL11, CXCR3, and SLC39A1, were found to be potential downstream targets. Two subsequent studies in Chinese postmenopausal women also reported increased miR‐133a levels in serum and plasma of low BMD group …”
Section: Mirnas In Human Osteoporosis Studiesmentioning
confidence: 88%
See 1 more Smart Citation
“…The study has provided experimental and clinical evidence to delineate the role of miRNAs in regulating osteolytic bone metastasis. It is interesting to note that miR‐133a was found to inhibit osteoclast differentiation and resorption activity in vitro, in contrast to the aforementioned positive regulatory role of miR‐133a in osteoclasts, which may attribute to the different disease mechanism between osteoporosis and cancer bone metastasis. In addition, our laboratory has identified that miR‐214‐3p was significantly upregulated in bone specimens from breast cancer patients with osteolytic bone metastasis .…”
Section: Mirna Osteoclastogenesis and Bone Resorptionmentioning
confidence: 96%
“…Li and colleagues detected the upregulated miR‐133a in serum isolated from postmenopausal osteoporosis patients, which was negatively correlated with the patients’ lumbar bone mineral density (BMD). They demonstrated that miR‐133a knockdown could inhibit the RANKL‐induced osteoclastogenesis in vitro and alleviated the bone loss in ovariectomized rats in vivo.…”
Section: Mirna Osteoclastogenesis and Bone Resorptionmentioning
confidence: 99%